Perancangan dan Pengukuran Kinerja Rantai Pasok Produk Alat Kesehatan dengan Supply Chain Operations Rerenrence (Scor) - Tiena Gustina Amran; Valianto Gonawan (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
In general, good Supply Chain Management (SCM) provides benefits, namely customer satisfaction, increasing revenue, decreasing costs, increasing asset utilization, increasing profits. In a medical equipment company, one of the products produced is Gris Emergency Trolley 3 Drawer. There are products returned by consumers and delays in sending them, indicating that the company's supply chain needs improvement with the first step in measuring performance. The purpose of this study is to design a performance measurement system and measure the supply chain performance of Gris Emergency Trolley 3 Drawer using the SCOR (Supply Chain Operations Reference) method. SCORcards uses 5 perspectives as indicators for measuring SCM performance, namely supply chain reliability, supply chain responsiveness, supply chain agility, supply chain costs and supply chain asset management. Based on the results of SCORcards performance measurement there are 2 perspectives whose performance is still low, namely the perspective of Supply Chain Reliability with the Perfect Order Fullfilment metrics having attainment of 22.29%, metric of Orders Delivered in Full having an achievement of 57.96%, Delivery Performance to Customer Commitment having 66.89%, the overall perspective of Supply Chain Reliability obtained a value of 2.69, which means that this perspective is in fairly good condition. Supply Chain Cost Perspective with Supply Chain Management Cost (as a Precentage of Revenue) metric has 66.70%, Sold Cost of Goods (as a Precentage of Revenue) has 88.41% and metrics Cost to Return has an achievement of 15%, overall perspective Supply Chain Cost has a value of 2.13 which means that this perspective is in a bad condition.